2014
DOI: 10.1016/j.devcel.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Sox5 Is a DNA-Binding Cofactor for BMP R-Smads that Directs Target Specificity during Patterning of the Early Ectoderm

Abstract: SUMMARY The SoxD factor, Sox5, is expressed in ectodermal cells at times and places where BMP signaling is active, including the cells of the animal hemisphere at blastula stages, and the neural plate border (NPB) and neural crest (NC) at neurula stages. Sox5 is required for proper ectoderm development, and deficient embryos display patterning defects characteristic of perturbations of BMP signaling, including loss of neural crest and epidermis and expansion of the neural plate. We show that Sox5 is essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…Smad1, Smad5 and Smad8) in chondrocytes leads to severe chondrodysplasia (Retting et al, 2009), indicating that BMP signaling is necessary not only for the initiation of chondrogenesis but also for the maintenance of this differentiation program. Recently, BMP-regulated Smads were demonstrated to regulate gene expression in early Xenopus embryos via interaction with Sox5 (Nordin and Labonne, 2014). This study demonstrated that both Sox5 and Sox6 could bind to Smad1 (Nordin and Labonne, 2014), so it seems plausible that these transcription factors may also transduce BMP signals to activate chondrogenic differentiation.…”
Section: Tgfβ Signaling In Chondrogenesismentioning
confidence: 94%
See 1 more Smart Citation
“…Smad1, Smad5 and Smad8) in chondrocytes leads to severe chondrodysplasia (Retting et al, 2009), indicating that BMP signaling is necessary not only for the initiation of chondrogenesis but also for the maintenance of this differentiation program. Recently, BMP-regulated Smads were demonstrated to regulate gene expression in early Xenopus embryos via interaction with Sox5 (Nordin and Labonne, 2014). This study demonstrated that both Sox5 and Sox6 could bind to Smad1 (Nordin and Labonne, 2014), so it seems plausible that these transcription factors may also transduce BMP signals to activate chondrogenic differentiation.…”
Section: Tgfβ Signaling In Chondrogenesismentioning
confidence: 94%
“…Recently, BMP-regulated Smads were demonstrated to regulate gene expression in early Xenopus embryos via interaction with Sox5 (Nordin and Labonne, 2014). This study demonstrated that both Sox5 and Sox6 could bind to Smad1 (Nordin and Labonne, 2014), so it seems plausible that these transcription factors may also transduce BMP signals to activate chondrogenic differentiation. Lyons and colleagues noted that the chondrocyte-specific knockout of Bmpr1a and Bmpr1b resulted in both defective maturation of chondrocytes, from a resting to a columnar proliferating state, and in an inability of hypertrophic chondrocytes to complete terminal differentiation (Yoon et al, 2006).…”
Section: Tgfβ Signaling In Chondrogenesismentioning
confidence: 94%
“…16 However, both direct Wnt/b-Catenin target genes, tfap2a and gbx2, are already expressed at that stage and in the case of tfap2a this early expression also depends on BMP signaling. 30,32,38 Moreover, tfap2a induction in na€ ıve ectodermal explants required only low levels of Wnt/ b-Catenin activity, 30 suggesting that low endogenous activity is sufficient to induce tfap2a in the NPB. During gastrulation, NPB genes apparently exhibit differential sensitivity toward Wnt/b-Catenin signaling.…”
Section: Wnt Signalingmentioning
confidence: 99%
“…30 In blastula and early gastrula stage Xenopus embryos, tfap2a is expressed in the entire non-neural ectoderm and the prospective NPB territory and a recent study showed that this expression depends on BMP activity. 31,32 The source of BMP ligands is likely the non-neural ectoderm or the prospective NPB ectoderm itself, which expresses BMP ligands in zebrafish, frog, chick and mouse embryos. 28,[33][34][35] Consistently, the potential of epidermis to induce NPB or NC is supposedly attributable to the expression of BMP ligands.…”
Section: Bmp Signalingmentioning
confidence: 99%
“…A potential candidate for binding to the M4 site is the SoxD family member, Sox5, previously implicated in cranial neural crest formation in chick and Xenopus (Perez-Alcala et al, 2004, Nordin and LaBonne, 2014). Consistent with previous reports (Perez-Alcala et al, 2004), we observed Sox5 expression as early as stage HH7 in the forming cranial neural folds and its expression becomes more pronounced when neural crest cells arise at stage HH9-10.…”
Section: Resultsmentioning
confidence: 99%